Implementasi Program Unggulan Tahfidz Dalam Meningkatkan Hafalan Siswa Smp Alhikmah Sirampog - Nema Mafruhatul Ulya; Didi Nur Hilal; Abdul Azis; Adi Purnama Alam (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe the implementation of the Qur’anic tahfidz excellence program in improving students’ memorization at SMP Al Hikmah Sirampog and to identify the supporting and inhibiting factors in its implementation. The tahfidz Al-Qur’an program is one of the school’s flagship programs oriented toward improving the quality of students’ memorization while also developing their religious character. This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation. The research subjects included the principal, tahfidz coordinator, tahfidz teachers, and students participating in the tahfidz program. The findings reveal that the implementation of the tahfidz program at SMP Al Hikmah Sirampog consists of three main stages: planning, implementation, and evaluation. In the planning stage, the school determines memorization targets, arranges activity schedules, and prepares competent tahfidz teachers. The implementation stage is carried out routinely through several methods, such as talaqqi, ziyadah, muraja’ah, and halaqah, to improve both the quality and quantity of students’ memorization. Program evaluation is conducted periodically through memorization deposits, tajwid assessment, and fluency evaluation. Supporting factors include a religious school environment, strong school management support, student motivation, and active involvement of tahfidz teachers. Meanwhile, the inhibiting factors include limited time, differences in students’ memorization abilities, and inconsistency in muraja’ah activities. Overall, the tahfidz excellence program has made a positive contribution to improving students’ Qur’anic memorization at SMP Al Hikmah Sirampog.